Signal Transduction Profiling of Angiotensin II Type 1 Receptor With Mutations Associated to Atrial Fibrillation in Humans - Simões, Sarah C.; Balico-Silva, André L.; Parreiras-e-Silva, Lucas T.; Bitencourt, André L. B.; Bouvier, Michel; Costa-Neto, Claudio M. (Frontiers in Pharmacology, 2020)
The AT1 receptor (AT1R) has a major role in the Renin-Angiotensin System, being involved in several physiological events including blood pressure control and electrolyte balance. The AT1R is a member of the G protein coupled receptors (GPCR) family, classically known to couple Gαq and engage β-arrestin recruitment. Both G protein and arrestin signaling pathways are involved in modulation of different downstream kinases. A previous study reported that mutations in the AT1R (A244S and I103T-A244S) were positively correlated with higher risk of atrial fibrillation in men. Based on that report, we aimed to investigate if these mutations, including I103T only, could affect AT1R signal transduction profile, and consequently, implicate in atrial fibrillation outcome. To address that, we engineered an AT1R carrying the above-mentioned mutations, and functionally evaluated different signaling pathways. Phosphokinase profiler array to assess the mutations downstream effects on kinases and kinase substrates phosphorylation levels was used. Our results show that the I103T-A244S mutant receptor presents decreased β-arrestin 2 recruitment, which could lead to a harmful condition of sustained Gαq signaling. Moreover, the phosphokinase profiler array revealed that the same mutation led to downstream modulation of kinase pathways that are linked to physiological responses such as fibrous tissue formation, apoptosis and cell proliferation.